Nutrient intakes and metabolomic profiles associated with animal source energy percentage in children’s diets - Topi Hovinen; Elina Kettunen; Maijaliisa Erkkola; Anu Suomalainen; Riitta Freese; Liisa Korkalo (Scientific Reports)
Abstract The purpose of the study was to calculate the relative intake of animal source energy (animal source energy percentage, ASEP) and examine its utility in nutrition and metabolic research with a special attention on children. In addition, the capacity of ASEP to identify potential metabolic biomarkers of plant-forward diets was tested. Four-day food records and 7-day dietary screeners of 51 Finnish children aged 1–7 years, consuming a vegan (n = 7), pesco-/lacto-/ovo-vegetarian (n = 11) or omnivorous diet (n = 33), were used for assessing general performance of ASEP as diet measure. Blood samples of 40 children (six vegans, eight vegetarians, 26 omnivores) were analyzed for plasma LDL cholesterol, erythrocyte folate concentration and serum untargeted MS-metabolomics. Estimated ASEPs varied between 0% and 52%. Vegetarians and omnivores showed overlapping ASEPs. ASEP had a strong positive correlation with saturated fatty acid (percent of energy, E%; r = 0.785) and cholesterol intake (r = 0.715) and a strong negative correlation with fibre (r = − 0.811) and polyunsaturated fatty acid (E%; r = − 0.819) intake. ASEP also correlated with plasma LDL cholesterol (r = 0.699) concentration. Serum indoleacrylic acid (IAA) is suggested to be further investigated as a possible biomarker of plant-forward diet. ASEP provides a useful tool for objective and quantitative assessment of diet characteristics in research.